Comportamento do esforço cortante à fadiga em vigas de concreto armado - Silva, José Eudes Marinho da (2019)
Fatigue is an important degradation process, which can manifest itself intensely in cyclically loaded structures such as road bridges, approach slabs, wind towers and offshore structures. The existing equations for calculating the strains of reinforced concrete beams under fatigue loading are scarce. The objective of this work is to evaluate the behavior of reinforced concrete beams to the shear stress under fatigue loading and to propose an equation for calculating strains of the stirrups under fatigue. An experimental program was designed to test 12 reinforced concrete beams with a length of 3.50 m and a rectangular section of 15 x 35 cm, divided into four groups, one of them with beams without transverse reinforcement. The applied load was constant and the smaller load was 10% of the last load resistant. The parameters varied in the experimental program were transversal reinforcement rate (0.119%, 0.189% and 0.378%) and the relationship between the maximum applied stress and the static strength of the beams (0.50 and 0.60). It was verified that with the change in the relation between the maximum tension applied and the static strength of the beams from 0.50 to 0.60, there was little influence on the behavior of the strains of the reinforced concrete beams in the fatigue tests. After obtaining the experimental data and the literature data, it was possible to establish an equation for the calculation of the strain of reinforced concrete beams under fatigue loading.